(untitled) (Journal of Libya for geographical studies, 2022)
The study aims to know the climatic characteristics of annual and seasonal evaporation rates in the Misurata region, assess the impact of climate change on annual and seasonal evaporation rates and reveal their recent trends, by analyzing their monthly data for the period from 1963-2018, at the Misurata Climatic Station using several statistical methods, including: Moving averages, Cumulated Sums, Simple Linear Regression and t-test. The study concluded that there is a discrepancy in the characteristics of evaporation rates monthly, quarterly and annually in the Misurata region, with the emergence of trends for an increase in annual and seasonal rates at a statistical significance level of less than 0.001 except for the summer season, which showed a trend of increase without statistical significance.